Comparison of four nutritional screening tools in perioperative elderly patients: Taking orthopedic and neurosurgical patients as examples - Gong, Jie; Zuo, Silu; Zhang, Jie; Li, Li; Yin, Jie; Li, XinYi; Yu, Fengmei; Hu, Wen (Frontiers in Nutrition, 2023)
Background & aims: Malnutrition is widely present in elderly surgical patients and is highly correlated with prognosis after surgery. However, no research comparing the effectiveness of comprehensive nutritional screening tools in geriatric surgical patients has been published. We assessed the nutritional risk among elderly orthopedic and neurosurgical surgical patients and their associated clinical indicators and outcomes using four screening tools. The aim of this study was to explore optimal tools for screening nutritional status and predicting prognostic indicators. Methods: The Nutritional Risk Score 2002 (NRS2002), Mini Nutritional Assessment - Short Form (MNA-SF), Geriatric Nutritional Risk Index (GNRI), and Prognostic Nutritional Index (PNI) were all performed within two days of admission and before surgery. The relationships between nutritional risk classifications and conventional nutritional markers, complications and LOS were evaluated. Results: A total of 167 orthopedic patients and 103 neurosurgical patients were analyzed in this study. In neurosurgical patients, the rates of malnutrition or at risk of malnutrition were 26.4%, 24.6%, 8.4% and 12.6%, respectively, according to the MNA-SF, GNRI, NRS2002 and PNI. According to the NRS2002 and GNRI, the rates of old neurosurgical patients who were malnourished or at risk of malnutrition were 14.6% and 15.5%, respectively, which are still lower than the results assessed by the MNA-SF (24.3%) and GNRI (15.5%). Multiple regression analysis revealed a significant relationship between the PNI (malnourished vs.well-nourished, OR=5.39, 95%CI :1.11-26.18, P=0.037), GNRI (at risk vs.no risk, OR=3.96, 95%CI :1.01-15.45, P=0.048) and the complications in orthopedic patients. Only GNRI was significantly related to LOS>7 days (at risk vs.no risk, OR=4.01, 95%CI :1.64-9.80, P=0.002). For neurosurgical patients, an association between GNRI and LOS>8 days was discovered (at risk vs.no risk, OR=3.35, 95%CI :1.03-10.86, P=0.002). Conclusions: The GNRI was considered the best nutritional screening tool for predicting short-term outcomes in elderly perioperative orthopedic and neurosurgical patients. More research is necessary to determine its applicability in other surgical fields.